African swine fever at the wildlife-livestock interface: challenges for management and outbreak response within invasive wild pigs in the United States - Brown, Vienna R.; Miller, Ryan S.; Pepin, Kim M.; Carlisle, Keith M.; Cook, Merril A.; Vanicek, Cole F.; Holmstrom, Lindsey K.; Rochette, Lisa T.; Smyser, Timothy J. (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) causes significant morbidity and mortality in both domestic and wild suids (Sus scrofa), and disease outbreaks convey profound economic costs to impacted industries due to death loss, the cost of culling exposed/infected animals as the primary disease control measure, and trade restrictions. The co-occurrence of domestic and wild suids significantly complicates ASF management given the potential for wild populations to serve as persistent sources for spillover. We describe the unique threat of African swine fever virus (ASFV) introduction to the United States from epidemiological and ecological perspectives with a specific focus on disease management at the wilddomestic swine interface. The introduction of ASF into domestic herds would require a response focused on containment, culling, and contact tracing. However, detection of ASF among invasive wild pigs would require a far more complex and intensive response given the challenges of detection, containment, and ultimately elimination among wild populations. We describe the state of the science available to inform preparations for an ASF response among invasive wild pigs, describe knowledge gaps and the associated studies needed to fill those gaps, and call for an integrated approach for preparedness that incorporates the best available science and acknowledges sociological attributes and the policy context needed for an integrated disease response.